2012
DOI: 10.1177/039463201202500213
|View full text |Cite
|
Sign up to set email alerts
|

A Validated HPLC Method for the Monitoring of Thiopurine Metabolites in Whole Blood in Paediatric Patients with Inflammatory Bowel Disease

Abstract: Therapeutic drug monitoring (TDM) of major metabolites of thiopurine drugs is a widely used tool for assessing treatment efficacy and toxicity in patients with inflammatory bowel disease (IBD). We report the laboratory and clinical validation of a simple and reliable high performance liquid chromatography (HPLC) method for the measurement of 6-thioguanine nucleotides (6-TGN) and 6-methylmercaptopurine (6-MMP) on paediatric patients with IBD. The aim of this paper is to develop and validate a method for the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Fifteen studies fulfilled the eligibility criteria . ‘Potentially’ eligible studies which were assessed and subsequently excluded are shown in http://onlinelibrary.wiley.com/doi/10.1111/bcp.12365/suppinfo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies fulfilled the eligibility criteria . ‘Potentially’ eligible studies which were assessed and subsequently excluded are shown in http://onlinelibrary.wiley.com/doi/10.1111/bcp.12365/suppinfo.…”
Section: Resultsmentioning
confidence: 99%
“… and Cangemi et al . did not reach any conclusions due to very few reported cases. Therefore, a weak association between WBC and thiopurine metabolite concentrations was described in three studies ( n = 126 patients), inconclusive results were reported by four studies ( n = 120 patients) due to very few or no reported cases, and a possible inverse correlation between 6TGN and WBC was suggested by three studies ( n = 263 patients).…”
Section: Monitoring Of Thiopurine Toxicitymentioning
confidence: 87%
See 1 more Smart Citation
“…[7][8][9] The reasons for discrepancies have not been found to date and remain to be explored. Hence, whether therapeutic drug monitoring of thiopurines should be used in clinical practice is still a matter of debate.…”
mentioning
confidence: 99%
“…Currently, various kinds of analytical methods including high-performance liquid chromatogrphy, electrochemical method, phosphorimetry, localized surface plasmon resonance, fluorimetry, and SERS [9][10][11][12][13][14][15] have been reported for the determination and quantification of 6-TG. In fact, these analytic methods were thought to be rapid and sensitive, but they also show their limitations and demerits such as high cost, complicate separation process, tedious pretreatment steps and sophisticated instrumentation.…”
Section: Introductionmentioning
confidence: 99%